Sosialisasi Keamanan Password Dalam Menggunakan Internet Bagi Para Santri Majelis Ta’lim Faizul Haq - Ibnu Rusdi; Maryanah Safitri; Sita Anggraeni; Tyas Setiyorini (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
Almost all activities today can be done online. The internet has provided convenience in many ways and provides access to information quickly anywhere. However, various dangers can arise, including data theft, intellectual property theft, sabotage, and many more. Therefore, internet users must be aware of the crimes that exist on the internet. One way is to maintain the security of user passwords on the internet. After the community service was held in the form of counseling regarding password security tips on the internet, now the students of the Faizul Haq Ta'lim assembly get broader and very useful knowledge about internet security. They can apply tips and tricks in maintaining password security on the internet life in their daily lives.